Enhancing Communication Learning as a Self-Improvement Vehicle for Content Creators in Indonesia - Purwani, Diah Ajeng (UPT Publikasi Ilmiah UNISBA, 2025)
Students often face significant challenges when working on their theses, with many experiencing stress and other constraints during this phase. These struggles are frequently highlighted in media coverage. The TikTok account @Ira Mira, managed by a lecturer, offers an innovative approach to help students better prepare for thesis work. By providing relaxed and engaging learning opportunities in a virtual space, this account has created a supportive virtual community that aids students in overcoming academic hurdles. This study explores the role of learning communication through TikTok, specifically analyzing the content created by @Ira Mira to support final-year students. Using virtual ethnography and direct interviews, the research examined 633 pieces of content published between January 2021 and December 2023, including videos, photos, conversations, and other interactions on the platform. The findings reveal that Ira Mira, as the content creator, actively refines her learning communication strategies on TikTok and adapts to evolving social media trends to better cater to the needs of her student audience. This approach has fostered new ideas and strategies for thesis completion among her followers. The implications of this study underscore the importance of continuous improvement in learning communication for educators and content creators which will allow them to provide greater value and support to their audiences.